Efektivitas Aplikasi Islami Terhadap Muslim Generasi Z dalam Meningkatkan Kemampuan Membaca Al-Qur’an - Ari Hartawan (Jurnal Studi Al-Qur'an, 2022)
As a generation that lives in the era of technological development, Generation Z sees smartphones no longer as devices but more as a lifestyle. The rapid growth of technology makes the smartphones that they hold offer many innovations that can facilitate all aspects of their lives, including worship by reading the Al-Qur'an through Islamic applications. It is believed that an Islamic application with various features and flexibility can improve the user's Al-Qur'an reading ability, especially the technology-savvy Generation Z. By involving 85 Muslim respondents of generation Z through an online survey, this study seeks to find out how practical Islamic applications are to increase the skills of reading the Al-Qur'an for generation Z Muslims. Various opinions of respondents are presented and then categorized so that these opinions result from a percentage stating that Islamic applications are declared quite effective to improve Gen Z's skills in reading the Al-Qur'an.